Inhibition of Phosphodiesterase-4 Reverses Aβ-Induced Memory Impairment by Regulation of HPA Axis Related cAMP Signaling - Xu, Ying; Zhu, Naping; Xu, Wen; Ye, Han; Liu, Kaiping; Wu, Feiyan; Zhang, Meixi; Ding, Yun; Zhang, Chong; Zhang, Hanting; O'Donnell, James; Pan, Jiangchun (Frontiers in Aging Neuroscience, 2018)
Beta amyloid peptides (Aβ) is found to be associated with dysfunction of hypothalamic-pituitary-adrenal axis (HPA axis) that leads to memory and cognitive deficits in Alzheimer’s disease (AD) patients. Phosphodiesterase 4 (PDE4) inhibitors increase the intracellular cAMP activities, which may ameliorate cognitive deficits associated with AD. However, it remains unclear whether PDE4-mediated reversal of cognitive impairment in mouse model of AD is related to HPA axis and downstream cAMP-dependent pathway. The present study investigated the effects of PDE4 inhibitor rolipram on Aβ 1-42-induced cognitive dysfunction and its underlying mechanisms. The step-down passive avoidance (PA) and Morris water-maze (MWM) tests were conducted 1 week (1 W), two months (2 M) and six months (6 M) after intracerebroventricular microjection (i.c.v.) of Aβ 1-42. The results suggested that memory impairment emerged as early as 1 W, peaked at 2 M, and lasted until 6 M after injection. Chronic treatment with rolipram (0.1, 0.5, 1.0 mg/kg/d, i.p.) for 2 weeks (i.e. treatment started at 1.5 months after Aβ 1-42 microinjection) dose-dependently improved memory performance in both MWM and PA tests. Moreover, rolipram reversed Aβ-induced increases in serum corticosterone (CORT), corticotropin-releasing factor and glucocorticoid receptors (CRF-R and GR) levels; while decreases in brain derived neurotropic factor (BDNF) and the ratio of pCREB to CREB expression. These effects of rolipram were prevented by pre-treatment with PKA inhibitor H89. The findings indicated that the protective effects of rolipram against Aβ 1-42-induced memory deficits might involve HPA axis and cAMP-CREB-BDNF signaling.